Effect of Probiotics on Infantile Colic in Breast-Fed Infants: A Randomized Single-Blind Clinical Trial - Roohanizadeh, Hamed; Karami, Hasan; Hashemi, Seyyed Abbas (International Journal of Child Health and Nutrition, 2019)
Aim: This study examined the impact of probiotics on children’s colic in breast-fed infants. Methods: This study was a randomized single-blind clinical trial. 100 infants were referred to pediatric gastroenterology clinic of Avicenna diagnosed by gastroenterologist of children who suffered from infantile colic and they were qualified after justifying parents and obtaining written consent. (IRCT registration number: IRCT2016082829573N1). Results: Results showed that there was a statistically significant difference in terms of crying time (p = 0.000) and the arrival and departure of the group. (p = 0.000). Conclusion: The outcomes indicated that using probiotics could reduce colic in infants and improve the quality of life in this group